2021
DOI: 10.1038/s41398-020-01123-7
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly detection to predict relapse risk in schizophrenia

Abstract: The integration of technology in clinical care is growing rapidly and has become especially relevant during the global COVID-19 pandemic. Smartphone-based digital phenotyping, or the use of integrated sensors to identify patterns in behavior and symptomatology, has shown potential in detecting subtle moment-to-moment changes. These changes, often referred to as anomalies, represent significant deviations from an individual’s baseline, may be useful in informing the risk of relapse in serious mental illness. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…More specifically, Barnett et al 147 followed 17 patients with psychosis using a passive monitoring app installed on their smartphone for up to three months, and identified anomalies in mobility patterns and social behavior in the two weeks prior to relapse. A further study in 83 patients with psychosis using digital markers found similar results 30 . This was also observed in a study (N=60) using a neural network approach 148 .…”
Section: Evidence For Digital Psychiatry Within Specific Contextssupporting
confidence: 69%
See 2 more Smart Citations
“…More specifically, Barnett et al 147 followed 17 patients with psychosis using a passive monitoring app installed on their smartphone for up to three months, and identified anomalies in mobility patterns and social behavior in the two weeks prior to relapse. A further study in 83 patients with psychosis using digital markers found similar results 30 . This was also observed in a study (N=60) using a neural network approach 148 .…”
Section: Evidence For Digital Psychiatry Within Specific Contextssupporting
confidence: 69%
“…For instance, relapse risk in schizophrenia may be foreseen by "anomaly detection", which involves the use of smartphone sen sor data to monitor divergences of an individual's behavioral patterns compared to his/her personal baseline. Preliminary studies in small samples have found reasonable sensitivity and specificity from applying this approach to date 30 .…”
Section: Smartphone Sensor Data and Digital Phenotypingmentioning
confidence: 95%
See 1 more Smart Citation
“…The error components are then used to build Hotelling's T-squared test statistic and identify anomalies. Henson et al [25] applied the method and achieved 89% sensitivity and 75% specificity for predicting relapse in schizophrenia in a cohort of 126 participants followed by 3 to 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of data collections during inpatient treatment for schizophrenia could help to quantify symptom development and treatment response. This would allow for the partial decryption of the disorder and identify patients that are at great risk to relapse (Henson et al, 2021;Torous et al, 2018). Ideally, this data is assessed digitally as it can be stored directly in the patient's electronic medical record and the clinical staff has a direct access to the patients' All rights reserved.…”
Section: Introductionmentioning
confidence: 99%